PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Resvan; Refor Diansyah; Tari Indriani; Syukron Wahyudhi; Wulan Purnamasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is one of the basic literacy skills that elementary school students need to master. However, in reality, many students still have difficulty understanding the content of reading texts in depth. This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on the reading comprehension ability of elementary school students. The method used in this research is a quasi-experimental design with a nonequivalent control group design. The study population was all fourth-grade students of SDN 09 Pontianak Timur totaling 56 students, consisting of 28 students in the experimental class and 28 students in the control class selected using purposive sampling technique. The research instrument was a multiple-choice test that had been tested for validity and reliability. Data were analyzed using independent t-test and N-Gain score. The results showed that the average pretest score of the experimental class was 52.14 and the control class was 51.07, while the average posttest score of the experimental class increased to 80.36 and the control class to 65.71. The N-Gain value of the experimental class was 0.59 in the moderate category, while the control class was 0.30 in the low category. The t-test results showed a significant difference between the experimental and control classes (p < 0.05). Thus, it can be concluded that the Problem Based Learning model has a positive and significant effect on improving the reading comprehension ability of elementary school students.